The COVID-19 pandemic should be last orders for poor care of people with neurodevelopmental disorders. (June 2021) - Strydom, Andre; Corcoran, Elizabeth; Rebillat, Anne-Sophie
Summary: We explore whether the needs of individuals with neurodevelopment disorders have been overlooked during the coronavirus disease 2019 (COVID-19) pandemic and set out the issues that need to be considered in response to future health crises and pandemics.